Selection Of Employee Recruitment Based On Priority Sequence Level Assessment Using ROC Method - Rachmat; Siti Nur Asia; Muhammad Yusuf; Suherwin (Institute of Computer Science (IOCS), 2022)
The organization runs a recruitment procedure to maintain the caliber of its workforce. The success or failure of a company's operations is largely determined by the success of its recruitment efforts or the acceptance of a big offer. In practice, the recruiting process frequently does not employ a selection system with predetermined evaluation criteria and an objective evaluation of each applicant. Therefore, this study applies decision-making approaches to the recruitment selection process by calculating the final alternative value using the Rank Order Centroid(ROC) method. The ROC technique can score and ascribe factors depending on the order of importance, resulting in more objective decision outcomes. The three best alternative employees that passed the selection were derived from the final computation of the alternative ranking based on five assessment factors.